Cinema Illuminating Reality: Media Philosophy through Buddhism - Ng, Teng-Kuan (The journal of religion and film, 2025)
This is a book review of Victor Fan, Cinema Illuminating Reality: Media Philosophy through Buddhism (Minneapolis: University of Minnesota Press, 2022)